Microvessel density and VEGF, HIF‐1α expression in primary oral melanoma: correlation with prognosis. (27th December 2012) - Simonetti, O; Lucarini, G; Rubini, C; Goteri, G; Zizzi, A; Staibano, S; Campanati, A; Ganzetti, G; Di Primio, R; Offidani, A
Abstract : Objective: To understand the role of angiogenesis and hypoxia in cancer progression of primary oral melanoma (POM). Materials and Methods: Sixteen malignant primary melanomas were immunostained with markers CD34, VEGF and HIF‐1α. Stained cells were counted in the invasive front and inside the tumour, and the differences were compared and correlated with histological parameters and disease‐specific survival of the patients. Results: Tumour invasive front showed increased MVD and increased vessel VEGF and HIF‐1α expression compared with the intratumoural compartment. No such differences were seen in tumoural melanocytes of the two compartments. Positive correlations were observed between CD34 and VEGF, CD34 and HIF‐1α and VEGF and HIF‐1α expression in invasive front vessels. CD34 expression was statistically correlated with the level of infiltration. A significant trend to worse disease‐free survival was also determined with increased invasive front vessel expression of CD34, VEGF and HIF‐1α. Conclusions: Our data highlight the importance of the invasive margin in POM biology. The high angiogenic activity and endothelial VEGF and HIF‐1α expression in invasive front vessels have a significant impact on patient survival and future agents targeted against VEGF pathway may represent a novel and effective therapeutic opportunity. Larger studies are needed to further address our findings.